2016
DOI: 10.1177/0706743716649188
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Health of Women with Intellectual and Developmental Disabilities and Comorbid Mental Illness

Abstract: Objective: Women with intellectual and developmental disabilities (IDD) have high rates of adverse perinatal outcomes. However, the perinatal health of women with co-occurring IDD and mental illness (dual diagnosis) is largely unknown. Our objectives were to 1) describe a cohort of women with dual diagnosis in terms of their social and health characteristics and 2) compare their risks for adverse maternal and neonatal outcomes to those of women with IDD only. Method: We conducted a population-based study using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 43 publications
3
26
0
Order By: Relevance
“…Our results were also in line with Darney et al’s [ 28 ] work in a retrospective cohort of all live births in California from 2000–2010 (gestational diabetes: 8.1%; caesarean delivery: 38.0%). In the Ontario health system from 2002–2010, Brown et al [ 29 ] found lower rates of gestational diabetes (3.2%) and gestational hypertension (1.2%) compared to our findings with similar rates of caesarean delivery (27.0%). With these consistent results, obstetricians should be aware of the high risk of maternal morbidity when treating pregnant women with IDD and researchers need to continue to investigate mechanistic pathways and IDD-specific interventions and preventive programs.…”
Section: Discussionsupporting
confidence: 50%
“…Our results were also in line with Darney et al’s [ 28 ] work in a retrospective cohort of all live births in California from 2000–2010 (gestational diabetes: 8.1%; caesarean delivery: 38.0%). In the Ontario health system from 2002–2010, Brown et al [ 29 ] found lower rates of gestational diabetes (3.2%) and gestational hypertension (1.2%) compared to our findings with similar rates of caesarean delivery (27.0%). With these consistent results, obstetricians should be aware of the high risk of maternal morbidity when treating pregnant women with IDD and researchers need to continue to investigate mechanistic pathways and IDD-specific interventions and preventive programs.…”
Section: Discussionsupporting
confidence: 50%
“…There is clear evidence-based guidance on the detection and treatment of perinatal mental disorders in the general population,5 6 but little evidence on vulnerable subgroups who may have distinct clinical presentation and/or service needs. In the two selected studies, population-based regional Canadian data are used to investigate perinatal mental health among migrant women (focusing on their postnatal use of mental health services compared with non-migrant women),7 and among women with intellectual or developmental disabilities (IDD) (focusing on adverse maternal and neonatal outcomes among women with comorbid IDD and mental illness compared with women with IDD only) 8…”
Section: Setting the Scenementioning
confidence: 99%
“…The physical, social and psychological demands of caring for a newborn can increase vulnerability to many health problems, including depression and anxiety. Moreover, mothers’ health and well-being during postpartum may exert lasting effects on themselves and their newborns 14. It is reasonable to suspect that the rates of postpartum psychiatric emergencies among women with IDD reported here are an underestimate.…”
Section: Discussionmentioning
confidence: 76%